Addition of Ammonium Acetate to Protein-Borax Baited Traps Does Not Improve Attraction of Anastrepha obliqua or Anastrepha serpentina (Diptera: Tephritidae). Issue 6 (12th November 2021) - Lasa, Rodrigo; Williams, Trevor
Abstract: Ammonia is considered a key component in the attraction of tephritid flies to protein-based lures. The addition of ammonium acetate to improve hydrolyzed protein-borax mixtures used to monitor tephritids has not been evaluated, although it has improved attraction to toxic baits. The presence of ammonium acetate crystals in a ventilated tube inside a trap containing hydrolyzed protein + borax, did not improve the capture of Anastrepha obliqua or Anastrepha serpentina flies in field experiments when compared with hydrolyzed protein + borax alone. In contrast, the addition of 1% ammonium acetate into the drowning solution of a hydrolyzed protein + borax mixture resulted in significantly reduced captures of both pests. Laboratory tests indicated that the emission of ammonia gas was increased 1.6–4.5-fold from traps that included ammonium acetate. These results confirm the hypothesis that a higher release of ammonia does not improve the attraction of tephritids when protein-derived odors are also present.